Tuberculous Bronchopleural Fistula: A Rare and Life-Threatening Disease - Lefika Bathobakae MD, MPH; Aneeqa Shahid MD; Tyler Wilkinson MSc; Devina Adalja MD; Jessimar Sanchez MD; Michael Agnelli MD; Jin Suh MD, FACP, FIDSA; Roberto Solis MD (SAGE Publishing, 2023)
Tuberculous bronchopleural fistula (BPF) is a rare and potentially life-threatening complication of pulmonary tuberculosis, in which abnormal connections form between the bronchial tree and the pleural space. These abnormal connections allow air and secretions to pass from the lungs into the pleural space, causing a range of symptoms from benign cough to acute tension pneumothorax. The management of tuberculous BPF requires an individualized approach based on the patient's condition and response to treatment. Anti-tuberculosis therapy is essential for controlling the active tuberculosis infections. Intercostal drainage and suction are also commonly used to drain air and fluid from the pleural space, providing relief from the symptoms. For some patients, more invasive surgeries, such as decortication, thoracoplasty or pleuropneumonectomy are required to definitively close the fistula when medical management alone is insufficient. Herein, we describe a rare case of tuberculous BPF in a young adult female, who was treated with anti-tuberculosis medications and open thoracotomy.